2015
DOI: 10.1111/crj.12314
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lung volumes and gas trapping in patients with large hiatal hernia

Abstract: Increasing HH size correlates with reduced TLC and VC. Surgery improves lung volumes and gas trapping; however, the changes are mild and within the normal range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…Airway narrowing and closure lead to gas trapping and ventilation inhomogeneity [38]. While gas trapping and airway closure can be inferred from an elevated RV/TLC ratio [39], a recently developed method to assess airway closure is oscillometric evaluation of respiratory system impedance. In a comparative study of lung mechanics in obese versus non-obese people with asthma, Salome et al found that obesity does not alter methacholine responsiveness measured by spirometry but significantly reduces respiratory system reactance and increases respiratory system resistance (Rrs) [32].…”
Section: The Effect Of Obesity On Airway Narrowing and Airway Closurementioning
confidence: 99%
“…Airway narrowing and closure lead to gas trapping and ventilation inhomogeneity [38]. While gas trapping and airway closure can be inferred from an elevated RV/TLC ratio [39], a recently developed method to assess airway closure is oscillometric evaluation of respiratory system impedance. In a comparative study of lung mechanics in obese versus non-obese people with asthma, Salome et al found that obesity does not alter methacholine responsiveness measured by spirometry but significantly reduces respiratory system reactance and increases respiratory system resistance (Rrs) [32].…”
Section: The Effect Of Obesity On Airway Narrowing and Airway Closurementioning
confidence: 99%
“…This strategy is supported by an only modest observed improvement in pulmonary function tests after hernia repair. Objectively, there was significant post-operative increase in TLC and VC, with no significant alteration in the RV (4,9). Improvements in TLC and VC were proposed secondary to the physical removal of gastric tissue from the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences were observed between the ITS categories, with an increase in post-operative TLC in the overall group and patients (9). The FVC and FEV 1 are other objective pulmonary functions which showed significant improvement in the majority of studies (4,5,9). Improvement of the FVC and FEV 1 theoretically represent the relief of both airway obstruction due to gastric compression of respiratory outlets and decreased restriction due to increased volume available for lung expansion (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, plethysmograph tends to count as TGV any air that is within the thoracic cage as it is compressed by the panting manoeuver 1. We usually think that only the air volume being above the diaphragm is counted but in case of diaphragmatic hernia, hiatal hernia2 or major colonic dilation,3 subdiaphragmatic air being forced up into the thoracic cage is also taken into account. In the present case, TGV measured both intrathoracic gases, which increased after colonic exsufflation, and subdiaphragmatic gases, decreased by exsufflation, resulting in a non-significant change in TGV.…”
mentioning
confidence: 99%